POTRET KEADILAN DISTRIBUTIF: KONTRIBUSI ZAKAT DAN INFAK DALAM MEREDUKSI KETIMPANGAN PENDAPATAN DI INDONESIA - Ahmad Muhammad Khoirul Anam; Muhlis (IAIN BONE, 2025)
Income inequality is a crucial structural issue in Indonesia's development, marked by a trend in the Gini Ratio that has remained relatively stagnant around 0.38 since 2020. This condition indicates that conventional policy interventions have not been entirely effective, necessitating alternative instruments of distributive justice, namely Zakat and Infaq, which are theoretically designed to redistribute wealth from the affluent (aghniya) to the rightful recipients (mustahik). This study aims to empirically analyze the role of Infaq Receipts (X1), Infaq Disbursement (X2), Zakat Receipts (X3), and Zakat Disbursement (X4) on the Gini Ratio (Y) as a proxy for income inequality in Indonesia.Using the multiple linear regression analysis method on time series data, the results show that the regression model is simultaneously significant in affecting the Gini Ratio (Sig.=0.037) with a strong predictive power (R Square=0.830). This indicates that 83.0% of the variation in inequality can be explained by Zakat and Infaq activities. However, partially (t-test), most variables do not significantly influence the Gini Ratio (X1, X3, and X4), suggesting that the current volume or mechanism of Zakat and Infaq funds is not yet statistically strong or efficient enough to significantly reduce widespread inequality. The only variable showing an indication of influence is Infaq Disbursement (X2), which is significant at α=0.10 (Sig.=0.076), but with a positive coefficient (B=0.001). This counter-intuitive finding highlights the need for an in-depth review of the effectiveness and targeting of Infaq disbursement, which might still be oriented towards short-term consumption, thus failing to fundamentally narrow the economic gap. This research recommends strengthening the strategic disbursement of Zakat and Infaq towards productive programs to maximize their contribution to realizing distributive justice in Indonesia.